PENGARUH PRICE EARNING RATIO , CAPITAL ADEQUACY RATIO DAN LOAN TO DEPOSIT RATIO TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Siti Fatiatur Rohma; Ika Wahyuni; Triska Dewi Pramitasari (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to examine the influence of Price Earnings Ratio (PER), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR) on stock prices and firm value in banking sector companies listed on the Indonesia Stock Exchange (IDX). The research employed the Partial Least Square (PLS) method assisted by SmartPLS 3.0 software, involving the coefficient of determination test, structural model analysis (inner model), and hypothesis testing. The results show that Price Earnings Ratio (PER) has a positive but insignificant relationship with stock prices. Capital Adequacy Ratio (CAR) has a negative and insignificant effect on stock prices, while Loan to Deposit Ratio (LDR) has a negative and significant effect on stock prices. Regarding firm value, Price Earnings Ratio (PER) and Capital Adequacy Ratio (CAR) have positive but insignificant effects, whereas Loan to Deposit Ratio (LDR) has a negative but insignificant effect on firm value. Furthermore, stock price has been proven to have a positive and significant effect on firm value. The results of the indirect effect analysis indicate that PER and CAR are unable to influence firm value through stock prices, while LDR has a negative and significant effect on firm value through stock prices. This study is expected to provide a reference for investors in making investment decisions and serve as a consideration for companies in improving firm value and financial performance.